2016
DOI: 10.1016/j.schres.2016.01.034
|View full text |Cite
|
Sign up to set email alerts
|

How sedentary are people with psychosis? A systematic review and meta-analysis

Abstract: ObjectiveSedentary behaviour (SB) is an independent risk factor for cardiovascular disease and mortality. We conducted a meta-analysis to investigate SB levels and predictors in people with psychosis. MethodMajor electronic databases were searched from inception till 09/2015 for articles measuring SB with a self-report questionnaire (SRQ) or objective measure (e.g. accelerometer) in people with psychosis, including schizophrenia spectrum and bipolar disorders. A random effects meta-analysis and meta regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
165
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 243 publications
(179 citation statements)
references
References 35 publications
8
165
2
1
Order By: Relevance
“…The literature suggesting the deleterious impact of sedentary behavior among people with schizophrenia is relatively sparse, although clearly there are concerns given the recently reported high levels [16]. Previous Stubbs et al [17] demonstrated among 250 people with established psychosis of similar age to the current study that higher levels of sedentary behavior were independently associated with increased C reactive protein [17].…”
Section: Accepted M Manuscriptmentioning
confidence: 45%
See 1 more Smart Citation
“…The literature suggesting the deleterious impact of sedentary behavior among people with schizophrenia is relatively sparse, although clearly there are concerns given the recently reported high levels [16]. Previous Stubbs et al [17] demonstrated among 250 people with established psychosis of similar age to the current study that higher levels of sedentary behavior were independently associated with increased C reactive protein [17].…”
Section: Accepted M Manuscriptmentioning
confidence: 45%
“…Sedentary behavior is defined as any waking activity characterized by an energy expenditure ≤ 1.5 metabolic equivalents including tasks such as sitting or reclining posture [15]. A recent meta-analysis demonstrated that people with schizophrenia spend approximately 12.5 hours a day being sedentary which is among the highest in any population in the world [16]. Two studies have suggested that self-report sitting behavior is associated with adverse metabolic profile [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In an exploratory study among 60 adult outpatients with bipolar disorder, patients were sedentary for approximately 13.5h per day according to accelerometers worn over seven consecutive days (Janney et al, 2014). This is more than double the level of sedentary behavior reported in older populations (>60 years) (mean=5.3h per day) (Harvey et al, 2014) and similar to the levels found in people with psychosis (Stubbs et al, 2016). The extent to which sedentary behavior in people with bipolar disorder contributes to the previously observed physical fitness impairments (Vancampfort et al, 2015c; and metabolic abnormalities (Vancampfort et al, 2015d), both predictors for cardiovascular diseases and premature mortality (Lee et al, 2010), is unknown.…”
Section: Introductionmentioning
confidence: 58%
“…First, the present research used a self-report questionnaire to assess sitting time in volunteers, and hence may underestimate overall sitting time. Previous research in people with psychosis (Stubbs et al, 2016) already demonstrated that objective measurement of sedentary behavior predicts higher levels of sedentariness. Participants in the current study reported sitting approximately 7 hours per day, whilst total sedentary time (including lying down) was recorded as almost double (13.5 hours) in a recent study utilizing objective measurement (Janney et al, 2014).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Among schizophrenia patients, they are highly related to obesity due to several factors such as antipsychotic medication [2], physical inactivity [3,4] and poor dietary intake [5,6]. Obesity is a well-known global burden on health and to make it worst the number tend to increase from year to year and Malaysia as a developing country is not excluded from having the same problem [7].…”
Section: Introductionmentioning
confidence: 99%